Publisher Correction: Evidence that CD32a does not mark the HIV-1 latent reservoir. (29th November 2018) - Osuna, Christa; Lim, So-Yon; Kublin, Jessica; Apps, Richard; Chen, Elsa; Mota, Talia; Huang, Szu-Han; Ren, Yanqin; Bachtel, Nathaniel; Tsibris, Athe; Ackerman, Margaret; Jones, R.; et al.
In this Brief Communications Arising Comment, the first three authors (Osuna, Lim and Kublin) should have been listed as equally contributing authors; this has been corrected online.